Six Approaches in the Study of the History of Psychology - León Donayre, Ramón Alberto (2021)
The courses of history of psychology at the universities are suffering a reduction (instead two semesters only one now). In this communication the author discusses the importance of the history of psychology asignatures and shows the most important approaches to the historical research in psychology: the biographical, the chronological, the problem-oriented, the social,  the contrafactic.  and the history of apparats.